A retrospective review of sagittal split ramus osteotomy: Incidence and risk factors for neurosensory disturbance of the inferior alveolar nerve - Takuma Watanabe; Shu Inoue; Risa Okada; Ryuji Uozumi; Michinobu Sasaki; Tatsuya Kawamura; Shizuko Fukuhara; Makoto Hirota (PLoS ONE, 2026)
Sagittal split ramus osteotomy (SSRO) is the most commonly performed mandibular procedure in orthognathic surgery. Although generally safe, neurosensory disturbance (NSD) of the inferior alveolar nerve (IAN) remains a frequent complication that can impair oral function and quality of life. This retrospective study included 463 patients who underwent SSRO, comprising 873 rami, at our department between 2014 and 2024. Patient- and ramus-level variables were extracted from electronic medical records, with postoperative NSD of the IAN defined as the primary outcome. We investigated the presence or absence of mandibular canal (MC)–lateral cortical bone (LCB) contact on preoperative computed tomography, as well as the three types of lateral osteotomy line on postoperative panoramic radiographs. Descriptive statistics were used to summarize clinical characteristics, and the incidence of NSD was evaluated. Trends in annual NSD proportions were analyzed using a Cochran–Armitage trend test, and univariable and multivariable logistic regression analyses were performed to assess associated factors. The incidence of NSD was 5.6% at the patient-level and 4.0% at the ramus-level. A decreasing trend in annual NSD incidence was observed (p < 0.001). In multivariable analysis, the presence of MC–LCB contact was strongly associated with NSD (odds ratio, 4.96; 95% confidence interval, 2.41–10.06; p < 0.001). The incidence of NSD after SSRO was approximately 5% and showed a declining annual trend over time, possibly reflecting increasing surgical experience and improved instrumentation. MC–LCB contact was associated with an approximately fivefold higher risk of NSD, highlighting the importance of careful and gentle osteotomy.